The smart effort to build up an innovative organizational culture in a skincare company - Handoko, Yunus; Anjaningrum, Widiya Dewi (Jurnal Siasat Bisnis, 2024)
Purpose – The research objective was to examine the predominant errand of work engagement (WE) and the physical work environment (PWE) in the development of innovative organizational culture (IOC) by contemplating the mediating factors of innovative work behaviour (IWB) and employee performance (EP).Design/methodology/approach – The research was conducted through a questionnaire survey of all employees of PT. Alzena Skincare Indonesia, 175 people who produced quantitative primary data. Through the PLS-SEM high-level analysis, the validity and reliability of the questionnaire were checked, and each research hypothesis was evaluated in detail.Findings – The research results showed that an ‘IOC’ in a skincare company can be developed, and ‘WE’ is the principal aspect. However, it was still essential for the company to heed the ‘PWE’. The partial mediating role of ‘IWB’ and ‘EP’ accelerated the formation of an ‘IOC’. Meanwhile, serial mediation of ‘IWB’ and ‘EP’ only supported ‘WE’ in building ‘IOC’, not the ‘PWE’.Research limitations/implications – This research was still limited to PT. Alzena Skincare Indonesia employees, so the results cannot be generalized to other types of businesses. Thus, further research is compulsory to test the research model on other objects and look for other factors that can encourage creation of an innovative organizational culture.Practical implications – The practical implication of this research was that skincare company managers need to build ‘IOC’ by strengthening ‘WE’ and improving the ‘PWE’ that supports it. These two factors created ‘IWB’ and improved ‘EP’, ultimately forming an ‘IOC’.Originality/value – It still needed to uncover research that examined the effect of ‘WE’ and the ‘PWE’ on ‘IOC’, especially if it was serially mediated by ‘IWB’ and ‘EP’. So, the complex model was the main novelty of this study.